Evaluation of the serum free light chain (sFLC) analysis in prediction of response in symptomatic multiple myeloma patients: rapid profound reduction in involved FLC predicts achievement of VGPR. (14th June 2014) - Hansen, Charlotte T.; Pedersen, Per T.; Nielsen, Lars C.; Abildgaard, Niels
Abstract Background Observational data from clinical studies indicate that the goal of first‐line therapy in newly diagnosed patients with symptomatic multiple myeloma (MM) should be very good partial response (VGPR) or better, preferably before high‐dose treatment. We evaluated the value of early measurements of involved free light chains (iFLC) in prediction of high‐quality responses. Measuring iFLC has a potential advantage due to a short half‐life compared to the half‐life of the M‐protein. Methods In 36 multiple myeloma (MM) patients, we measured serial changes in iFLC and M‐protein after start of treatment. iFLC and M‐protein were measured before treatment, the following 5 wk days, 2, 3 and 6 wks after start of treatment. Results Median iFLC and M‐protein half‐life was 2.75 and 11.9 d, respectively. All patients with an iFLC >75 mg/L had an initial significant reduction (>20%) in iFLC, even patients with no response to treatment. The mean per cent reduction in iFLC 3 d after start of treatment was 52.3% and 23.6% (P = 0.021) in patients achieving ≥VGPR and PR, respectively. The mean per cent reduction in M‐protein in patients achieving ≥VGPR and PR was not significantly different in the 6‐wk study period. As a predictor of VGPR, an 80% reduction in iFLC at day 21 resulted in a sensitivity of 87.5% and a specificity of 100%. Conclusion Changes in iFLC could be a tool for early identification of responders to anti‐myeloma therapy. Early, sequential measurements of iFLC within the first week after start of treatment are not meaningful.